COMPLIANCE IN PAYING TAX PERSPECTIVE TAXPAYER ATTRIBUTES AND SANCTIONS - Suci Mafaza (Inovasi, 2022)
Awareness of paying taxes is the result of many factors, ranging from knowledge about taxes to the benefits of taxes received. Therefore, the government needs to make more efforts to win the hearts of the people so that awareness of paying taxes increases. Several things that need to be done are about how to motivate through friendly and pleasant tax services, to imposing sanctions on taxpayers who are clearly absent. The purpose of this research is to look at some of the internal and external factors that may influence the awareness of paying taxes. This study applies quantitative techniques with numerical data as a basis for drawing conclusions. The research data were processed using moderating-based regression statistical techniques. The research sample is 100 respondents, who are taxpayers in the South Jakarta area. The sampling technique was carried out by simple random sampling by distributing questionnaires. The results of the study state that awareness of paying taxes is a condition in which taxpayers are aware of their role in contributing to national development through taxes. Therefore, emotional factors such as providing motivation and tax services are one of the stimuli that strengthen awareness of paying taxes. Likewise with sanctions, sometimes some people feel reluctant to pay taxes, so imposing sanctions is an effective thing to do.Keywords:   Taxpayers, Tax Awareness, Desire to Pay Taxes, Services and Sanctions, National Development, Financial Conditions